Genetic Polymorphisms and the Efficacy of Platinum-Based Chemotherapy: Review - Afifah NN; Diantini A; Intania R; Abdulah R; Barliana MI (Dove Medical Press, 2020)
Nadiya Nurul Afifah,1 Ajeng Diantini,1,2 Ruri Intania,3 Rizky Abdulah,1,2 Melisa I Barliana2,4 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, Indonesia; 2Center of Excellence in Higher Education for Pharmaceutical Care Innovation, Universitas Padjadjaran, Bandung, Indonesia; 3Dr. H.A. Rotinsulu Lung Hospital, Bandung, Indonesia; 4Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Melisa I BarlianaDepartment of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung Sumedang KM. 21, Jatinangor 45363, IndonesiaEmail melisa.barliana@unpad.ac.idAbstract: Previous studies have indicated that genetic variations in individuals may result in changes in gene expression and amino acids. The effect of these changes may lead to different responses to platinum-based chemotherapy. A vast response rate interval and a short survival rate indicate that the efficacy and efficiency of the selection of chemotherapy have not been optimized. This article aims to illustrate the potential relationship of various genetic polymorphisms in response to platinum-based chemotherapy for several types of cancer. This review was conducted using articles from the last three- and five-year periods (2014– 2019) that use gene polymorphism and its relationship to the efficacy of platinum-based chemotherapy as their theme. A total of 26 out of 488 relevant articles were included based on specific criteria. Through various mechanisms, genes, including ERCC1, ERCC2/XPD, XPC, XPA, XRCC1, APE-1, PARP1, OGG1, ABCC2, MRP, GSTP1, GSTM1, GSTT1, MATE1, and OCT2, have been associated with patient response to platinum-based chemotherapy. We conclude that genetic polymorphism analysis is recommended for the management of cancer so that each patient can be administered therapy based on his or her genetic profile to achieve an effective and efficient outcome.Keywords: genetic polymorphism, platinum-based chemotherapy, DNA repair, drug accumulation, drug detoxification